Lymph node harvest as a predictor of survival for colon cancer: A systematic review and meta-analysis - Simarpreet Ichhpuniani; Tyler McKechnie; Jay Lee; Jeremy Biro; Yung Lee; Lily Park; Aristithes Doumouras; Dennis Hong; Cagla Eskicioglu (Surgery in Practice and Science, 2023)
Background and Objectives: The number of lymph nodes found harboring metastasis can be impacted by the extent of harvest. Guidelines recommend 12 lymph nodes for adequate lymphadenectomy to predict long-term oncologic outcomes, yet different cut-offs remain unevaluated. The aim of this review was to determine cut-offs that may predict survival outcomes. Methods: Medline, Embase, and CENTRAL were systematically searched. Articles were included if they compared overall survival (OS) or disease-free survival (DFS) above and below a lymph node harvest cut-off. Studies solely examining rectal cancer or stage-IV disease were excluded. Pairwise meta-analyses using inverse variance random effects were performed. Results: From 2587 citations, 20 studies with 854,359 patients (51.9% female, mean age: 68.9) were included, with 19 studies included in quantitative synthesis. A lymph node harvest cut-off of 12 predicted improved five-year OS (7 studies; OR 1.11, 95% CI 1.08–1.14, p<0.00001). A cut-off as low as 7 was associated with improved five-year OS (2 studies; OR 1.16, 95% CI 1.08–1.25, p<0.0001) and DFS (3 studies; OR 1.66, 95% CI 1.32–2.10, p<0.00001). All cut-offs greater than 12 demonstrated improved survival. Conclusions: A lymph node cut-off of 12 distinguishes differences in five-year oncologic outcomes. Contrarily, lymph node harvests other than 12 have not been rigorously studied and thus lack the statistical power to derive meaningful conclusions compared to the 12-lymph node cut-off. Nonetheless, it is possible that a lymph node harvest cut-offs less than 12 may be adequate in predicting long-term survival. Further prospective study evaluating cut-offs below 12 are warranted.